(untitled) (Annals of Medical Research, 2021)
Aim: Obesity is one of the important public health concerns in both developed and developing countries, and may associate with increased risk of periodontitis. Present study aims to determine whether there is an association between periodontal disease and obesity in Turkish population.Material and Methods: This study is consisted of 950 participants included; 551 women and 399 men aged 18 to75 years. In all patients; probing depth (PD), clinical attachment level (CAL), bleeding on probing (BOP) and plaque index (PI) were recorded and radiographic examination was performed. Obesity and overweight were assessed by body mass index (BMI) and waist circumference (WC) using World Health Organization criteria. The covariates were categorized into three groups; 1- Socio-demographic variables, 2- Oral health behaviors, 3- General health status.Results: When the periodontal health status evaluations of 950 patients in our study were examined; 131 patients were healthy, 592 patients were diagnosed as gingivitis, and 227 patients were diagnosed as periodontitis. High waist circumference and body mass index were correlated with periodontal disease after adjusting co-varieties (p0.05).Conclusion: This positive association suggests that obesity is coherent with logically plausible role in the development periodontal disease.Keywords: Periodontal diseases; body mass index; waist circumference.